How COVID-19 has Exposed Cyber Risks in the Health Sector : Why a Paradigm Shift is Needed for Building Cybersecurity Resilience - World Bank (World Bank, Washington, DC, 2021)
Cyberattacks targeting public health and the health sector have increased significantly since the outbreak of the Coronavirus (COVID-19) pandemic in 2020, resulting in disruption to the operations of domestic healthcare systems and services, theft of medical records, and significant financial losses, elevating the need to bring cybersecurity to the forefront of the development agenda. A broad conceptualization of cybersecurity to include elements of malicious information campaigns will help facilitate a focus and better management of this rapidly developing phenomenon. This brief focuses on how Coronavirus (COVID-19) has exposed cyber risks in the health sector, and why a paradigm shift is needed for building cybersecurity resilience.